REKLAMASI LAHAN KRITIS BEKAS PENAMBANGAN EMAS MENGGUNAKAN METODE BIOREMEDIASI DAN FITOREMEDIASI - Liswara Neneng; Dewi Saraswati (EnviroScienteae, 2019)
Degraded land caused by gold mining activities in Central Kalimantan requires reclamation efforts, in order to restore of soil conditions, due to the damage of topsoil layer, lack of soil nutrients, and reduced of soil fertility. This research aim was to find an appropriate method of biological reclamation in ex gold mining area, by utilizing a combination of several types of microorganisms and mercury phytoremediator plants. The research is an experiment on a pilot scale at an ex gold mining site in Central Kalimantan. Bioremediation method has used a consortium of local isolates Klebsiella sp. and Pseudomonas sp., and the phytoremediation method was used Melastoma sp. and Cyperus sp. Dependent variables were soil mercury concentration and soil nutrients. The results showed the application of consortium microorganisms and mercury phytoremediator, were able to reduce soil mercury concentrations in averages 2.5 ppm, soil nutrient levels increased in averages 33%. These increased soil nutrients consist of potassium in averaged 73%, Mg in average 21%, Na in average 19.5%, and Fe in averaged 71%, when compared to controls. The application of consortium of microorganisms combined with mercury plant phytoremediator type Melastoma sp., able more to improve soil conditions in ex gold mining area compared to Cyperus sp.